2008
DOI: 10.1523/jneurosci.2831-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Progeny of Olig2-Expressing Progenitors in the Gray and White Matter of the Adult Mouse Cerebral Cortex

Abstract: Despite their abundance, still little is known about the rather frequent, constantly proliferating progenitors spread throughout the adult mouse brain parenchyma. The majority of these progenitors express the basic-helix-loop-helix transcription factor Olig2, and their number further increases after injury. Here, we examine the progeny of this progenitor population by genetic fate mapping using tamoxifen-inducible Cre-recombination in the Olig2 locus to turn on permanent reporter gene expression in the adult b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
571
8
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(627 citation statements)
references
References 52 publications
45
571
8
3
Order By: Relevance
“…For example, following brain ischemia due to permanent middle cerebral artery occlusion (MCAo), generation of both astrocytic and neuronal precursors from NG2 + cells was observed in adult NG2creBAC:ZEG double transgenic mice, in which enhanced green fluorescent protein (EGFP) is expressed in OPCs and their progeny, thus allowing to visualize their final phenotype [10]. However, conflicting data arise from the different transgenic mouse models employed, and the controversy around the multipotency and neurogenic potential of OPCs in vivo is still an open issue [11][12][13][14][15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…For example, following brain ischemia due to permanent middle cerebral artery occlusion (MCAo), generation of both astrocytic and neuronal precursors from NG2 + cells was observed in adult NG2creBAC:ZEG double transgenic mice, in which enhanced green fluorescent protein (EGFP) is expressed in OPCs and their progeny, thus allowing to visualize their final phenotype [10]. However, conflicting data arise from the different transgenic mouse models employed, and the controversy around the multipotency and neurogenic potential of OPCs in vivo is still an open issue [11][12][13][14][15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…ϩ precursors appear to have the highest capacity for proliferation in vivo after brain injury (Zaidi et al, 2004;Buffo et al, 2005;Dimou et al, 2008).…”
Section: Inhibition Of the Shh-gli Axis Reduces The Proliferating Olig2mentioning
confidence: 99%
“…Interestingly, the mouse cortex contains also a large fraction of oligodendrocyte precursors cells that are tightly associated with neurons and do not synthesize Mbp (Trotter et al, 2010). Fate-mapping studies in the mouse showed that although these cells are mostly quiescent, they can be activated to divide and can give rise to oligodendrocytes, to neurons in the piriform cortex, and also to astrocytes (Kim et al, 2007;Dimou et al, 2008;Rivers et al, 2008;Zhao et al, 2009). These cells, which have processes that contact neurons, were variably referred to as polydendrocytes or more generally as OPCs in the mouse and rat (Wolswijk and Noble, 1989;Nishiyama et al, 1999Nishiyama et al, , 2009Hermann et al, 2010).…”
Section: Olig2 Cells In the Parenchyma Of The Telencephalonmentioning
confidence: 99%